CERITA RAKYAT BALI (SATUA ) SEBAGAI MEDIA PEMBELAJARAN KEKRITISAN PENALARAN ANAK USIA SEKOLAH DASAR DAN PENDIDIKAN KARAKTER - I Nyoman Sadwika; I Nyoman Astawan (Widyadari : Jurnal Pendidikan, 2020)
Good entertainment which is packaged in the form of reading satua (stories) for children is very supportive and good for children’s characters. Satua has a good value form local genius from a region, this value very relevant and give a good impact for child development escepecially primary student. The aim of this paper is for developing satua as a critical learning media for primary student. Satua is one of the effective media for building children's character. Satua as part of the literature recognizes that it has a positive contribution to the development of children's personality, if one is given the involvement of instilling, fostering, developing, and even preserving the values ​​of character education.